Promoting subglottic secretion drainage: a quality improvement project in a UK critical care unit - Nicholas Weston Smith; Michael Spivey (BMJ Open Quality)
The aim of the study was to promote the practice of subglottic secretion drainage (SSD) in a UK critical care unit. SSD is a technique employed to reduce microaspiration of oropharyngeal secretions in patients with cuffed endotracheal airways. Aspiration of oropharyngeal secretions is the accepted cause of the majority of ventilator-associated pneumonia (VAP), a complication of invasive ventilation with high associated mortality. The plan–do–study–act methodology was employed. The local critical care patient database was searched for patients requiring mechanical ventilation via a tracheostomy tube with subglottic port in the 3 months prior to intervention. Patient records were interrogated for evidence of the practice of SSD. The intervention involved the introduction of a tracheostomy care bundle to be prescribed on insertion of a tracheostomy on the critical care unit, in combination with departmental teaching. The bundle included prompts for nursing staff to practise regular SSD and to complete a tracheostomy care plan at the end of shift. A total of 24 patients were included. A review of practice was conducted every 3 months for 1 year. This showed an improvement in documented evidence of SSD from 0% of days at baseline to 85.7% of days at 1 year. Implementation of a tracheostomy order set prescribing regular SSD resulted in an improvement in the practice of SSD in patients ventilated via tracheostomy. This has implications for patient outcomes and healthcare costs, given that SSD has been shown to reduce incidence of VAP.